Review of Carbon Capture Technology and Its Potential Application to Reduce Emissions In Heavy Equipment Exhausts - Mutiara Putri; Nyayu Aisyah; Sugiyanto Sugiyanto; Lety Trisnaliani (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
Carbon emissions from diesel engines, particularly those from heavy equipment, are a significant greenhouse gas emitter in industries such as construction, mining, and logistics. As global efforts toward decarbonization intensify, carbon capture technologies offer a solution to reduce global emissions. This paper conducts a literature review to explore current carbon capture technologies—including chemical sequestration, physical sequestration, and membrane separation—and evaluates their potential for integration with heavy equipment exhaust systems. Key considerations include system size, energy requirements, maintenance, and operational compatibility. Integration of exhaust heat recovery systems is also assessed as a complementary solution to address the high energy demands of carbon capture in the environment. Technical, economic, and regulatory challenges are discussed, along with potential innovations and use cases that could support future deployments. The findings indicate that although carbon capture is still in its infancy, targeted applications and modular designs supported by policy incentives could enable practical implementation in the near future. This review provides a foundation for future research, pilot projects, and system designs aimed at enabling sustainable operation of heavy equipment